2009
DOI: 10.1016/j.ejcts.2009.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy due to lung cancer results in a more pronounced activation of coagulation system than lobectomy

Abstract: Pneumonectomy was associated with significantly higher activation of coagulation system on the seventh postoperative day than lobectomy. TAT complex, TF and E-selectin are promising markers of extensive postoperative activation of coagulation and efficacy of antithrombotic prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We identified several patient-specific risk factors including older age and obesity as independent predictors of postdischarge VTE, consistent with other single-institution series [1,6,24]. Previous data have also established the causal relationship between performance of pneumonectomy and risk for VTE [16,25,26]. These conclusions are consistent with our analysis; however this manuscript is the first to identify the association between pneumonectomy and VTE risk in the postdischarge period, based on our review of the current literature.…”
Section: Commentsupporting
confidence: 89%
“…We identified several patient-specific risk factors including older age and obesity as independent predictors of postdischarge VTE, consistent with other single-institution series [1,6,24]. Previous data have also established the causal relationship between performance of pneumonectomy and risk for VTE [16,25,26]. These conclusions are consistent with our analysis; however this manuscript is the first to identify the association between pneumonectomy and VTE risk in the postdischarge period, based on our review of the current literature.…”
Section: Commentsupporting
confidence: 89%
“…The activation state persists during surgery and is independent of the anaesthetic agents used. These results confirm previous studies performed on patients undergoing major abdominal surgery for colon-rectal cancer [ 27 ], hepatic cancer resection [ 28 ], pneumonectomy for lung cancer [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…One study found that pneumonectomy had a more pronounced activation of coagulation than the lobectomy group on the 7 th postoperative day. 22 We considered that postoperative hypercoagulability on the 7th day could have more confounding factors than that on the 3rd day, such as the infection, on top of the stress of the surgery, but further research is needed to clarify the question.…”
Section: Discussionmentioning
confidence: 99%